Dinasti Abbasiyah: Studi Analisis Lembaga Pendidikan Islam - Mahfud Ifendi (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2020)
In various sources of historical books it is said that the Abbasiyah dynasty was the peak of the heyday of Islamic civilization. This article, it aims to describe the Islamic educational institutions at that time which indirectly supported the progress of the Abbasiyah dynasty to reach its peak. This type of research is qualitative research, and is included in the category of library research. The data collection technique uses discourse analysis from books, journal articles, magazines, or other information related to the study of Islamic educational institutions during the Abbasiyah dynasty. Than, the writing of this article was analyzed using the Milles and Huberman analysis model, with the flow of data reduction, data preparation and conclusion drawing. The results of the research in this article can be seen from the form and nature of education. Islamic educational institutions that existed during the Abbasiyah dynasty can be categorized into 3 types. Which consists of informal educational institutions; such as the houses of the scholars', non-formal educational institutions; such as Kutab, mosque, qurhur, bookstore, observatory, literary salun, library, ribath and zawiyah and formal educational institutions, for example, madrasas. A lot of educational institutions that exist shows that this is in accordance with the belief in Islam which requires studying and is considered a form of worship. Therefore the place to study is very diverse, not only focused on a particular place.